2008
DOI: 10.1007/s00268-008-9777-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Metastasectomy for Soft‐Tissue Sarcomas: Is It Justified?

Abstract: Patients who have hepatic metastases that are functionally and technically resectable should be considered for surgery because this treatment offers the chance for long-term survival (>5 years).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…This recurrence rate is significantly lower compared with the published data, which ranges from 59.3% to 94% [16,20,22,24]. In all of these studies the liver was found to be the most common site of recurrent disease, ranging from 43.7% to 88%.…”
Section: Recurrent Diseasementioning
confidence: 69%
See 2 more Smart Citations
“…This recurrence rate is significantly lower compared with the published data, which ranges from 59.3% to 94% [16,20,22,24]. In all of these studies the liver was found to be the most common site of recurrent disease, ranging from 43.7% to 88%.…”
Section: Recurrent Diseasementioning
confidence: 69%
“…However, on multivariate analysis, DFI of more than two years was the only predictor of outcome. This was reconfirmed in the recent publication of Rehders et al [22]. Pawlik et al concluded that patients who were treated with adjuvant chemotherapy had a longer median overall survival compared with those who underwent surgery alone [16].…”
Section: Prognostic Factorsmentioning
confidence: 83%
See 1 more Smart Citation
“…Four studies were excluded from our analysis (10)(11)(12)(13). Three of them reported results on additional malignancies and did not fulfill our inclusion criteria (10,11,13).…”
Section: Included and Excluded Studiesmentioning
confidence: 99%
“…Three of them reported results on additional malignancies and did not fulfill our inclusion criteria (10,11,13). The forth study in addition to including LM from various sarcomas also encompassed radiofrequency ablation as a therapeutic strategy (12).…”
Section: Included and Excluded Studiesmentioning
confidence: 99%